Study on degradation of marine product processing waste water by Zeolite/Bi/ZnO catalyst. Issue 1 (February 2019) - Liu, Jinghua; Yu, Xiaocai; Wang, Liping; Guo, Meicen; Zhu, Wanting; Chen, Jinfang
Abstract: Nano-supported Zeolite/Bi/ZnO photocatalyst was successfully prepared and characterized by XRD, SEM testing means. Under the visible light, the effects of different factors such as Bi/Zn loading concentration, calcination time, calcination temperature, initial concentration of ammonia nitrogen /COD, illumination time and catalyst dosage on degradation of ammonia nitrogen/COD in deep processing of seafood wastewater were investigated. Furthermore, by carrying out orthogonal experiment, the study explored the optimal reaction conditions of self-made photocatalyst in practical application. It can be concluded that the self-made photocatalyst has a good degradation effect on the deep processing wastewater of marine products with lower concentration of pollutants, obvious effect has been obtained on the treatment of deep processing wastewater of marine product containing lower concentration of pollutants. The optimal experimental conditions for the degradation of ammonia nitrogen concluded as follows: when the calcination temperature of photocatalyst was 600 °C, the calcination time was 4 h, the catalyst dosage was 0.8 g/L, the initial concentration of ammonia nitrogen was 100 mg/L, illumination time was 2 h, the degradation rate can reach 80.9%. And the optimal experimental conditions of degradation of COD was concluded: when the calcination temperature of photocatalyst was 500 °C, the calcination time was 4 h, the catalyst dosage was 1.0 g/L, initial concentration of COD was 540 mg/L, illumination time was 3 h, the degradation rate can reach 94.1%. The results showed that compared with ZnO photocatalyst and Bi/ZnO photocatalyst, the Zeolite/Bi/ZnO photocatalyst has a significant effect on the degradation of COD and ammonia nitrogen.